Bullying, a moral issue: Representations of self and moral disconnects - Paulino Tognetta, Luciene Regina [UNESP]; Aviles Martinez, Jose Maria; Luis da Fonseca Rosario, Pedro Jose Sales (Ministry Education & Science, 2016)
Understanding and evaluating the scope of psychological aspects in actions of violence called bullying can contribute to the discussion of educational interventions that promote the type of moral education desired by educational institutions to overcome the problem in question. Therefore, This paper analyzed the possible relationships between the participation of adolescents in bullying, their self-representations, and the way in which they self-regulate to morally connect or disconnect (to judge situations where a moral content is at stake). 2,600 students aged between 14 and 15 years attending public and private schools in the state of Sao Paulo, Brazil participated in this exploratory research. Students responded to a questionnaire that sought to identify their involvement in bullying; learn what representations they admire, identify engagement and disengagement pertaining to moral dilemmas of everyday life regarding bullying. Finally, the correlations between these three were analyzed. The results show that victims of bullying are not the most morally disengaged even though they have engagements and disengagements. They also show that subjects whose choices lack ethical values disengage morally in bullying situations, and, though with significant differences, are themselves bullies. It was also found that subjects who hold less value in their self-representations, have more moral disengagements. Thus, we conclude that the representations that subjects have from themselves, whether admiring ethical values or not, correlate with engagements or disengagements in moral scenarios of violence. The educational implications suggest public policies that consider bullying as a moral problem and invest in ethical training of individuals to overcome it.
Keywords: bullying; moral; self-representation; moral disengagement; self-regulation